Antimicrobial resistance genes in Actinobacillus pleuropneumoniae, Haemophilus parasuis and Pasteurella multocida isolated from Australian pigs. Issue 7 (July 2016) - Dayao, DAE; Gibson, JS; Blackall, PJ; Turni, C
Abstract : Objective: To identify genes associated with the observed antimicrobial resistance in Actinobacillus pleuropneumoniae, Haemophilus parasuis and Pasteurella multocida isolated from Australian pigs. Design: Isolates with known phenotypic resistance to β‐lactams, macrolides and tetracycline were screened for the presence of antimicrobial resistance genes. Procedure: A total of 68 A. pleuropneumoniae, 62 H. parasuis and 20 P. multocida isolates exhibiting phenotypic antimicrobial resistance ( A. pleuropneumoniae and P. multocida ) or elevated minimal inhibitory concentrations (MICs) ( H. parasuis ) to any of the following antimicrobial agents − ampicillin, erythromycin, penicillin, tetracycline, tilmicosin and tulathromycin − were screened for a total of 19 associated antimicrobial resistance genes (ARGs) by PCR. Results: The gene bla ROB‐1 was found in all ampicillin‐ and penicillin‐resistant isolates, but none harboured the bla TEM‐1 gene. The tet B gene was found in 76% (74/97) of tetracycline‐resistant isolates, 49/53 A. pleuropneumoniae, 17/30 H. parasuis and 8/14 P. multocida . One A. pleuropneumoniae isolate harboured the tet H gene, but none of the 97 isolates had tet A, tet C, tet D, tet E, tet L, tet M or tet O. A total of 92 isolates were screened for the presence of macrolide resistance genes. None was found to have erm A, erm B, erm C, erm 42, mph E, mef A, msr A or msr E. Conclusion: The current study has provided a genetic explanation for the resistance or elevated MIC of the majority of isolates of Australian porcine respiratory pathogens to ampicillin, penicillin and tetracycline. However, the macrolide resistance observed by phenotypic testing remains genetically unexplained and further studies are required.